Exoplanets in the Antarctic Sky. V. The Second Data Release of AST3-II/CHESPA and Newly Found Variables within the Southern Continuous Viewing Zone of TESS - Bixuan Zhao; Hui Zhang; Michael C. B. Ashley; Jiapeng Zhu; Huigen Liu; Zhouyi Yu; Dan Zhou; Bin Ma; Jeremy Mould; Robert A Wittenmyer; Xiangyan Yuan; Zhengyang Li; et al. (The Astrophysical Journal Supplement Series)
Located at Dome A, the highest point on the Antarctic plateau, China’s Kunlun station is a premier ground-based photometric observatory. Its cold, dry, and stable atmosphere allows continuous observation for over 40 days during polar winter, ideal for detecting short-period transiting exoplanets. Since 2008, the Antarctic Survey Telescopes (AST3) project has pursued the CHESPA program to search for exoplanet candidates. During the austral winters in 2016 and 2017, the AST3-II telescope surveyed fields located in the southern continuous viewing zone of the Transiting Exoplanet Survey Satellite (TESS). This paper presents the second data release from CHESPA, encompassing photometric data for over 85,000 bright ( m _i ≤ 15) stars. The survey achieved a photometric precision of approximately 2 mmag at optimal brightness levels. To illustrate the data quality, we present a catalog of 203 newly identified variable stars showing brightness variations over 5 mmag based on the 2017 observations, as compared to Data Release 1. Among these, 26 are newly recognized periodic variables that are not listed in the AAVSO database ( https://www.aavso.org/ ), and 86 are in the TESS Candidate Target List. These variables required rigorous examination to eliminate false-positive signals in the transiting exoplanets search.